(Dys)Prosody in Parkinson’s Disease: effects of medication and disease duration on intonation and prosodic phrasing - Frota, Sónia (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).